Settled dust assessment in clinical environment: useful for the evaluation of a wider bioburden spectrum - Viegas, Carla (2019)
The collection and analysis of settled dust samples from indoor environments has become one of several environmental sampling methods used to assess bioburden indoors. The aim of the study was to characterize the bioburden in vacuumed settled dust from 10 Primary Health Care Centers by culture-based and molecular methods. Results for bacterial load ranged from 1 to 12 CFU.g−1 of dust and Gram-negative bacteria ranged between 1 to 344 CFU.g−1 of dust. Fungal load ranged from 0 CFU.g−1 of dust to uncountable. Aspergillus section Fumigati was detected in 4 sampling sites where culture base-methods could not identify this section. Mucorales (Rhizopus sp.) was observed on 1 mg/L voriconazole. Three out of 10 settled dust samples were contaminated by mycotoxins. Settled dust sampling coupled with air sampling in a routine way might provide useful information about bioburden exposure.